Society of Behavioral Medicine (SBM) position statement: provide funding for incentive programs to expand healthy food offerings in SNAP-authorized small food stores. Issue 6 (17th November 2020) - Singleton, Chelsea R; Adeyemi, Oluwafikayo S; Parab, Kaustubh V; Roehll, Alexandra M; Flores, Edson; Adams, Ashley M; Quintiliani, Lisa M; Bell, Brooke M; Dulin-Keita, Akilah
Abstract: Individuals and families with limited access to healthy foods often experience increased risk for poor diet and chronic disease. Low-income communities are more likely to have a large number of small food stores (e.g., corner stores and dollar stores) compared to higher-income communities. Since many of these small food stores participate in the Supplemental Nutrition Assistance Program (SNAP), increasing healthy food offerings in these stores may expand healthy food retail in low-income communities. We recommend the provision of funding for incentive programs that encourage SNAP-authorized small food stores in low-income communities to expand their healthy food offerings. This programming should (a) provide seed grants to store owners to develop or reconfigure store infrastructure, (b) offer store owners technical assistance and educational materials on marketing strategies for promoting healthy food items to customers, and (c) give a tax break to SNAP-authorized small food stores in low-income communities that maintain a predetermined minimum stock of U.S. Department of Agriculture-recognized staple foods. Abstract : The Society of Behavioral Medicine supports the funding of incentive programs for SNAP-authorized small food stores to support the expansion and maintenance of healthy food retail in low-income communities.